Sensitivity of inhalation anesthetics isoflurane and sevoflurane for the drug-induced QT-interval prolongation in guinea pigs - Yoshinobu Nagasawa; Kaori Sakai; Rui Kurimoto; Satoshi Kawakami; Megumi Aimoto; Akira Takahara (Elsevier, 2020)
We investigated effects of isoflurane and sevoflurane on sparfloxacin-induced QT-interval prolongation in guinea pigs under the monitoring of electrocardiogram and monophasic action potential (MAP), which was compared with those of halothane or non-inhaled anesthetics ketamine/xylazine. Intravenous administration of sparfloxacin at 3 and 10 mg/kg prolonged the QT interval and MAP duration together with bradycardic action under 4 different anesthetic conditions. The order of extent of prolongation of corrected QT interval after the administration of sparfloxacin was isoflurane ≈ sevoflurane ≈ halothane >> ketamine/xylazine, whereas that of the MAP90 at a pacing cycle length of 300 ms was halothane ≥ isoflurane ≈ sevoflurane >> ketamine/xylazine. These results suggest that isoflurane and sevoflurane as well as halothane could sensitize the heart to sparfloxacin-induced QT interval prolongation in guinea pigs. Keywords: Isoflurane, Sevoflurane, Halothane, QT interval, Monophasic action potential